A User Evaluation Study: Do Participants' Personal Notes Help Us to Summarise Meetings?. (April 2014) - Bothin, Antje; Clough, Paul
<x xml:space="preserve">Abstract</x> We describe a novel user evaluation study on the value of people's personal meeting notes for a question‐answering task involving meeting data taken from the Augmented Multiparty Interaction (AMI) corpus. A survey on task perceptions and note‐taking strategies in meetings was also conducted. The results suggest that written notes taken by multiple meeting participants contain the majority of the most informative meeting information and are thus likely to support information systems that employ automatic meeting understanding and summarisation. The users were able to achieve 79% and 76% accuracy in the task with handwritten and typed notes respectively as information source. Contrary to that, they scored 36% accuracy only using short extracts from the meeting speech and 98% correctness using abstractive human model summaries. The survey showed that people are generally very experienced with attending meetings and note‐taking and usually record the most important meeting events in a concise way. This provides evidence for the fact that personal notes are suitable as keywords and indices into a meeting recording. In general, task results correlated positively with perceived success. Users liked well‐structured abstractive human reference summaries but found meeting speech extracts difficult to work with. However, they also disliked the appearance of the notes, in particular the fact that the handwritten ones were hard to read. This emphasises the need for the development of innovative handwriting recognition methods and user interfaces that employ new presentation techniques, for example, key area highlighting. Meeting participants would also benefit from corporate training for better communication and note‐taking skills. Copyright © 2014 John Wiley & Sons, Ltd.